Sustainable desalination handbook : plant selection, design and implementation - Gude, Veera Gnaneswar, 1978- (Butterworth-Heinemann, 2018)
Sustainable Desalination Handbook: Plant Selection, Design and Implementation provides the comprehensive knowledge base required for efficient and sustainable process design for existing and new desalination plants around the world. This valuable resource for understanding and utilizing the most recent developments in desalination technologies and methods addresses the necessary components, including process design and implementation, operational strategies, and novel discoveries that minimize environmental impacts. In addition, the book features essential illustrations, operational details, issues and potential solutions and sustainable management strategies for present and future desalination plants.